Cognition and brain oxygen metabolism improves after bariatric surgery-induced weight loss: A pilot study - Anwar, Nareen; Tucker, Wesley J.; Puzziferri, Nancy; Samuel, T. Jake; Zaha, Vlad G.; Lingvay, Ildiko; Almandoz, Jaime; Wang, Jing; Gonzales, Edward A.; Brothers, Robert Matthew; Nelson, Michael D.; Thomas, Binu P. (Frontiers in Endocrinology, 2022)
Objective The primary objectives of this pilot study were to assess cognition and cerebral metabolic rate of oxygen (CMRO2) consumption in people with severe obesity before (baseline), and again, 2- and 14-weeks after sleeve gastrectomy bariatric surgery. Methods Six people with severe/class 3 obesity (52 ± 10 years, five females, body mass index (BMI) = 41.9 ± 3.9 kg/m2), and 10 normal weight sex- and age-matched healthy controls (HC) (48 ± 6 years, eight females, 22.8 ± 1.9 kg/m2). Global CMRO2 was measured non-invasively using MRI and cognition using the Integneuro testing battery. Results Following a sleeve gastrectomy induced weight loss of 6.4 ± 2.5 kg (% total-body-weight-lost = 5.4) over two-weeks, cognition total scores improved by 0.8 ± 0.5 T-scores (p=0.03, 15.8% improvement from baseline). Weight loss over 14-weeks post-surgery was 15.4 ± 3.6 kg (% total-body-weight-lost = 13.0%) and cognition improved by 1.1 ± 0.4 (p=0.003, 20.6% improvement from baseline). At 14-weeks, cognition was 6.4 ± 0.7, comparable to 6.0 ± 0.6 observed in the HC group. Baseline CMRO2 was significantly higher compared to the HC (230.4 ± 32.9 vs. 177.9 ± 33.9 µmol O2/100 g/min, p=0.02). Compared to baseline, CMRO2 was 234.3 ± 16.2 µmol O2/100 g/min at 2-weeks after surgery (p=0.8, 1.7% higher) and 217.3 ± 50.4 at 14-weeks (p=0.5, 5.7% lower) after surgery. 14-weeks following surgery, CMRO2 was similar to HC (p=0.17). Conclusion Sleeve gastrectomy induced weight loss was associated with an increase in cognition and a decrease in CMRO2 observed 14-weeks after surgery. The association between weight loss, improved cognition and CMRO2 decrease should be evaluated in larger future studies.